2019
DOI: 10.1007/s40199-018-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Phage antibody library screening for the selection of novel high-affinity human single-chain variable fragment against gastrin receptor: an in silico and in vitro study

Abstract: Background As a membrane G protein coupled receptors (GPCRs) family, gastrin/cholecystokinin-2 receptor (CCK2R) plays a key role in the initiation and development of gastric cancer. Objectives Targeting CCK2R by immunotherapeutics such as single-chain variable fragments (scFvs) may provide an effective treatment modality against gastric cancer. Thus, the main objective of this study was to isolate scFvs specific to CCK2R. Methods To isolate scFvs specific to the CCK2R, we capitalized on a semi-synthetic divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Antibody isolation using the hybridoma technology or transgenic mice needs long-term immunization procedures and screening [ 32 ]. Phage display is a technology to select recombinant antibodies like scFvs that bind specifically to various target molecules such as proteins, peptides, cell-surface glycans, and receptors with high affinity [ 23 ]. Until now, 14 phage display-derived therapeutic antibodies have been approved by FDA and/or EMA that the first one was against anti-tumor necrosis factor α (TNFα), named adalimumab (Humira) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody isolation using the hybridoma technology or transgenic mice needs long-term immunization procedures and screening [ 32 ]. Phage display is a technology to select recombinant antibodies like scFvs that bind specifically to various target molecules such as proteins, peptides, cell-surface glycans, and receptors with high affinity [ 23 ]. Until now, 14 phage display-derived therapeutic antibodies have been approved by FDA and/or EMA that the first one was against anti-tumor necrosis factor α (TNFα), named adalimumab (Humira) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phage display technology has broadly been used for selection of recombinant antibody fragments. This technique makes it easy to select specific binders against various target molecules [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most of the studies on antibody generation via phage display describe the use of purified antigens, suggesting that this approach may be more successful in providing high-quality antibodies [52][53][54][55][56] . Accordingly, in the present study, 16 novel antibodies were generated with this strategy, of which four showed better diagnostic performance than the best of the initial four antibodies generated against cell fractions (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…pCFH was the ligand and Ab42 was the receptor whose CDRs was defined as the binding region in the docking calculation. The RMSD Cutoff and the Interface Cutoff were set to six and nine angstroms, respectively [27,28]. A total of 2000 docking poses and 100 cluster were generated.…”
Section: Methodsmentioning
confidence: 99%